Adjustment of Teenagers Who are Broken Home in LKSA (Child Social Welfare Institution) Payat Ibrahim District Lima Puluh Kota - Devita Adriani; Jera Ball; Wahidah Fitriani (World Psychology, 2022)
This study aims to determine the personal adjustment of teenagers who are broken home at LKSA Payat Ibrahim Regency of Lima Puluh Kota and to determine the social adjustment of teenagers who are broken home at LKSA Payat Ibrahim Regency of Lima Puluh Kota.). The type of research that the author uses is a descriptive qualitative research type. The results of the study show that 1) Personal adjustment in adolescents with broken homes in LKSA Payat Ibrahim, Lima Puluh Kota Regency, it was found that adolescents who came from broken home families had aspects of personal adjustment, the ability to accept themselves and aspects of realizing their strengths and weaknesses. 2) Social adjustment of broken home adolescents at LKSA Payat Ibrahim, Lima Puluh Kota Regency, it was found that (MA and CK) only had aspects of social adjustment regarding the ability to adjust to peers, foster mothers, and the community. Meanwhile (MR) has aspects of social adjustment regarding compliance with existing rules, values , and norms and the ability to adapt to peers, foster mothers, and society.